A study of compressive and impact properties of jute lamnate structure composite - Nor Azam Binti Ramlee (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This research was performed i the form of experimental study about sandwich panel composite structure. The sanwich specimen was prepared in configuration of Jute/Epoxy/Honeycomb Nomex, Jute/Epoxy/Polyvinyl Choloride (PVC) foam, Jute/Epoxy/Polyethylene Therhphthalate (PET) foam and Jute/Epoxy/Medium Density Fiberboad (MDF). the aim of this research is to evaluate the mechineical behavior of sandwich panel composite with different core material by conducting the low velocity impact test and flexural test (three piont bending)